Implementasi Algoritma Simple Additive Weighting dalam pemilihan penerima Beasiswa di UIN Ar-Raniry - Rahmat Musfikar; Delvia Maulida; Hazrullah Hazrullah (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2023)
The cost of education at tertiary institutions in Indonesia is relatively high for some groups of people. Indonesian government agencies are trying to reduce this problem. One of the ways is by providing scholarships. The large number of scholarship enthusiasts becomes a challenge for the scholarship manager in making decisions on scholarship recipients. Scholarship selection at UIN Ar-Raniry is undertaken manually, so it is less efficient in making decisions on scholarship recipients. Hence, Decision Support System is required in the selection of scholarship recipients so that it fits with the criteria. With the existence of predetermined criteria, the Simple Additive Weighting (SAW) method is employed in which this method is simple, the algorithm is not difficult, and produces precise and accurate analysis based on the specified criteria values and preference weights. This study aims to analyze the SAW algorithm in selecting KIP scholarships at UIN Ar-Raniry so that it can facilitate the selection process. This test is carried out by calculating the weight of the SAW method with the concept of the weighted sum of each alternative and all its attributes. Calculation of the best value ranking results obtained from all the alternatives used that are eligible to become KIP-College scholarship recipients. Hence, it can be concluded that by applying the SAW method in determining scholarship acceptance at UIN Ar-Raniry, it can help facilitate the selection of scholarships efficiently and effectively.